The estimation of the costs of children based on random equivalence scales - Kot, Stanisław Maciej (Oszacowanie kosztów utrzymania dzieci na podstawie losowych skal ekwiwalentności, 2020)
This paper measures the cost of children using the random equivalence scale (RES). From the general population perspective, the deterministic microeconomic equivalence scales appear as continuous random variables. The stude derived the distribution of RES, assuming the lognormal distribution of income. The truncated distribution of RES can account for possible economies of scale in income or expenditure. The positional measures of the truncated distribution of RES may serve as single equivalence scales. A society’s attitude towards inequality may help chose such scales. RES for Poland 2015 was estimated using microdata from the Household Budget Survey. Polish households exhibited a remarkable level of economies of scale in that year and the equivalence scales declined with expenditure. It was observed that the cost of bringing up a child is not constant; generally, it decreases with increasing household size
Śląski Przegląd Statystyczny = Silesian Statistical Review, 2020, Nr 18 (24), s. 163-181